KEMUNDURAN DAN KEHANCURAN DINASTI ABBASIYAH SERTA DAMPAKNYA TERHADAP DUNIA ISLAM KONTEMPORER - Amin, Muhammad (State Institute for Islamic Studies Batusangkar, 2016)
This paper examines the impact of the destruction of the Abbasid dynasty to the contemporary Islamic world. Abbasid dynasty setbacks caused by two factors, namely internal and external. Internal factors are the most dominant influence on deterioration of the Abbasid dynasty, which for Muslims to leave their religion. While external factors are the most dominant influence on deterioration of the Abbasid dynasty, namely: the Crusades and the Mongol army raid into the torritery of Islam. The impact of the destruction of the Abbasid dynasty to the contemporary Islamic world seen from the aspect of science, politics and economics. In the aspect of science, after the fall of the Abbasid Muslims are always behind in the field of science against the West. In the political aspect, when the Muslims led by a king who was a Syamanism (worshipers of sun) is Khulagu Khan, and the contemporary period the loss of the power of Islam as a superpower. Muslims are fragmented, Muslims colonized by the West, there is no caliphate. Meanwhile, in the economic field, after the fall of the Abbasid Muslims suffered poverty and the economy dominated by Western nations today.Keywords: Collapse, Abbasid Dynasty, Conteparary Islamic world